Relationship Breakdown and the Economic Welfare of Australian Mothers and their Children - Chapman, B; Gray, M (My University, 2007)
This paper provides estimates of the effects of divorce on the lifetime incomes of mothers. This is an issue that is not well explored in most countries, and has been essentially untouched empirically in the Australian context. The paper extends the existing literature, which has generally focused on the short-term economic implications of divorce for mothers. Simulations are used to provide insights into the impact of divorce for a host of disparate circumstances. It is found that the relative income costs of divorce differ greatly depending upon the relative earnings capacity of the mother and father. Women with a much lower earning capacity than their partner face particularly large income costs of divorce. It is also found that the relative income costs of divorce fall as the number of children increases. The importance of child support payment to the household income of mothers following divorce is highlighted and it is shown that the income of mothers would be higher if they received child support at levels commensurate with the government's non-resident parent child support rules, rather than the levels they report actually receiving.
Australian Journal of Labour Economics
Keywords: Families -- Mothers; Finance; Families; Families -- Formation and Dissolution; Families and relationships; Income, wealth and finances; Families; Finance; Mothers; Formation and Dissolution; Families and relationships; Income, wealth and finance